Extra-clause constituents and their linear ordering - Camacho, Roberto Gomes [UNESP]; Pezatti, Erotilde Goreti [UNESP] (Federal Univ Ceara, 2023)
The aim of this paper is to make a description of extra-clausal constituents (ECC) in Portuguese adopting Giomi and Keizer's (2020) position that these constituents, performing certain rhetorical functions on the textual surface, cannot be left in limbo by a theory focused on the principle of pragmatic adequacy like Functional Discourse Grammar (FDG). This paper's specific purpose is to show, on the one hand, the syntactically loose character of these constituents, which can appear in special positions, replicated or not, in the structure of Language Expression, and, on the other hand, the theoretical closeness between Rhetorical Structure Theory (RST) (MANN; THOMPSON, 1988; MANN et al., 1992; TABOADA; MANN, 2006) and GDF (HENGEVELD; MACKENZIE, 2008, in terms of the rhetorical function that ECCs exert. The analysis showed that, for GDF and RST, ECCs are never part of the Nuclear Discourse Act and therefore their position within Linguistic Expression, from the perspective of GDF, cannot be determined by differences in functional scope, either interpersonal or representational. As an important theoretical consequence, the fact that hierarchically oriented ordering is irrelevant for extra-clausal syntax explains why it is not possible to identify any absolute or relative position in the Language Expression layer to house ECCs.
Keywords: extra-clausal constituent; linear ordering; rhetorical relation